A case for redistribution? Income inequality and wealth concentration in the recent crisis (2014)
Several Nobel laureates economists have called for redistributive policies. This paper shows that there is a strong case for redistributive policies because the global increase of income inequality and wealth concentration was an important driver for the financial and Eurozone crisis. The high levels of income inequality resulted in balance of payment imbalances and rising debt levels. Rising wealth concentration contributed to the crisis because the increasing asset demand from the rich played a key role in the rise of the structured credit market and enabled poor and middle-income households to accumulate increasing amounts of debt. To tame the inherent instability of the current mode of capitalism it is necessary to reduce inequality.